2022
DOI: 10.1101/2022.02.21.22271185
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Understanding how the design and implementation of Online Consultations influence primary care outcomes: Systematic review of evidence with recommendations for designers, providers, and researchers

Abstract: Background Online consultations (OCs) allow patients to contact their care provider online, and have been promoted as a way to address increasing workload and decreasing workforce capacity in primary care. Globally, OCs have been rolled out rapidly due to policy initiatives and the COVID-19 pandemic, though there is a lack of evidence regarding how their design and implementation influence care outcomes. Objective Informed by existing theories, synthesise quantitative and qualitative research on: 1) outcomes … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 86 publications
(190 reference statements)
0
1
0
Order By: Relevance
“…3 In a recent review of 63 studies on primary care online consultation systems (11 of which were conducted during the pandemic), there was no quantitative evidence for the negative impact of online consultations on patient safety, but qualitative studies suggested varied perceptions of their safety. 4 Online consultations increased access to care and decreased patient costs but were also sometimes found to have negative impacts on provider costs, staff and patient workloads, patient satisfaction and care equity. For instance, some primary care staff have indicated that they believe that patients seek help more readily via online consultations than they would have done via office-based consultations, and this leads to increasing staff workload.…”
Section: Further Digital Transformation Is Needed To Make the Nhs Fut...mentioning
confidence: 99%
“…3 In a recent review of 63 studies on primary care online consultation systems (11 of which were conducted during the pandemic), there was no quantitative evidence for the negative impact of online consultations on patient safety, but qualitative studies suggested varied perceptions of their safety. 4 Online consultations increased access to care and decreased patient costs but were also sometimes found to have negative impacts on provider costs, staff and patient workloads, patient satisfaction and care equity. For instance, some primary care staff have indicated that they believe that patients seek help more readily via online consultations than they would have done via office-based consultations, and this leads to increasing staff workload.…”
Section: Further Digital Transformation Is Needed To Make the Nhs Fut...mentioning
confidence: 99%